1981
DOI: 10.1126/science.213.4505.340
|View full text |Cite
|
Sign up to set email alerts
|

Prokaryotic Cells in the Hydrothermal Vent Tube Worm Riftia pachyptila Jones: Possible Chemoautotrophic Symbionts

Abstract: The existence of a symbiotic association between vestimentiferan tube worms from deep-sea hydrothermal vents and chemoautotrophic sulfur-oxidizing prokaryotes, based on histological and enzymatic evidence, is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
313
0
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 628 publications
(324 citation statements)
references
References 26 publications
4
313
0
2
Order By: Relevance
“…Since the first discovery of a dense, unique and diverse ecosystem in deep-sea hydrothermal vents in 1977 (Corliss et al, 1979), many studies have shown that deep-sea vent invertebrates such as tubeworms and Bathymodiolus mussels are sustained nutritionally by intracellular symbiotic bacteria (endosymbionts) as primary producers (Cavanaugh et al, 1981(Cavanaugh et al, , 1987Felbeck, 1981;Childress et al, 1986). In addition, several species of deep-sea vent invertebrates harbour bacteria (epibionts) that colonize the surfaces of specialized tissues such as the dorsal setae of the polychaete Alvinella pompejana, the gill chambers of the shrimp Rimicaris exoculata and the setae of the galatheid crabs Shinkaia crosnieri, Kiwa hirsuta and K. puravida (Polz and Cavanaugh, 1995;Cary et al, 1997;Goffredi et al, 2008;Watsuji et al, 2010;Thurber et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Since the first discovery of a dense, unique and diverse ecosystem in deep-sea hydrothermal vents in 1977 (Corliss et al, 1979), many studies have shown that deep-sea vent invertebrates such as tubeworms and Bathymodiolus mussels are sustained nutritionally by intracellular symbiotic bacteria (endosymbionts) as primary producers (Cavanaugh et al, 1981(Cavanaugh et al, , 1987Felbeck, 1981;Childress et al, 1986). In addition, several species of deep-sea vent invertebrates harbour bacteria (epibionts) that colonize the surfaces of specialized tissues such as the dorsal setae of the polychaete Alvinella pompejana, the gill chambers of the shrimp Rimicaris exoculata and the setae of the galatheid crabs Shinkaia crosnieri, Kiwa hirsuta and K. puravida (Polz and Cavanaugh, 1995;Cary et al, 1997;Goffredi et al, 2008;Watsuji et al, 2010;Thurber et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Substrates for bacterial chemosynthesis, that is, oxygen, sulfide and carbon dioxide, are taken up from the diffuse flow fluids through the worm's plume and delivered to the symbionts, which are enclosed in specialized host cells (bacteriocytes) in an organ termed trophosome (Hand, 1987;Bright and Sorgo, 2003). Bacterial sulfide oxidation provides the energy that fuels CO 2 fixation into organic matter (Cavanaugh et al, 1981;Felbeck, 1981;Felbeck and Somero, 1982;Fisher and Childress, 1984;Childress et al, 1991;Girguis and Childress, 2006). With the publication of its metagenome (Robidart et al, 2008), the name Candidatus Endoriftia persephone was proposed for the Riftia symbiont.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to detect tube worm symbionts in host eggs and larvae by the use of microscopy and PCR have been unsuccessful (4)(5)(6)12), suggesting that transmission does not occur vertically. Furthermore, most vent vestimentiferan species host symbionts that share identical 16S rRNA sequences, which is also consistent with the hypothesis of environmental transmission (14,22).…”
mentioning
confidence: 99%